Hábitos nutricionales y su asociación con el estado nutricional en niños de educación básica de 7 a 14 años de dos instituciones educativas. - Castaño Rodríguez, Heidy Andrea; Erazo Jamioy, Zaira Julieth; Albañil Mora, Lucy Johana (Universidad Antonio Nariño, 2024)
Nutritional status is defined as the condition in which a balance is achieved between nutrient intake and the energy needs of the organism, which allows it to reach a certain degree of well-being; Currently, the world is experiencing a set of nutritional transformations that have caused a high rate of malnutrition, overweight and obesity in the population, as a result of which there is an increase in the consumption of ultra-processed foods rich in fats and sugars, which prevail especially in children and adolescents, having as a primary factor the consumption of these foods within their educational institutions affecting their healthy development, so it is necessary to determine how their nutritional status is related to this type of food. Having said this, a characterization form was used to characterize children from two educational institutions (private and public) from 7 to 14 years old, where information related to age, sex and socioeconomic level was obtained, also including information related to height and weight, in order to calculate the BMI and determine the nutritional status of children in basic education. On the other hand, an instrument entitled "lifestyle and nutrition", of which only the domain that covered nutritional habits was used. A prevalence of excess weight was found in the private institution and a greater alteration in height for age in the public institution.